The role of illness perceptions on medication nonadherence among patients with hypertension: A multicenter study in indonesia - Alfian, Sofa D.; Annisa, Nurul; Perwitasari, Dyah A.; Coelho, Andre; Abdulah, Rizky (Frontiers in Pharmacology, 2022)
Introduction: Nonadherence to antihypertensive medications is recognized as a significant cause of treatment failure. Therefore, identifying its underlying factors, particularly from the patient’s perspective, is essential for developing tailored intervention strategies. The objective of this study was to evaluate the associations between different domains of illness perception and medication nonadherence among patients with hypertension in Indonesia. Patients and methods: A multicenter cross-sectional study was conducted among patients with hypertension aged at least 18 years old who were using antihypertensive medications in the last 3 months in the community health centers in the 3 cities in Indonesia. The different domains of illness perception (consequences, timeline, personal control, treatment control, identity, concerns, comprehension, and emotional response) and medication nonadherence were assessed using a validated Brief Illness Perceptions Questionnaire (BIPQ) and Medication Adherence Report Scale (MARS), respectively. A logistic regression analysis was used to evaluate the associations between the different domains of illness perception and medication nonadherence adjusting for confounders. The odds ratios (ORs) with 95% confidence intervals (CIs) were reported. Results: A total of 440 participants were included, whom 41.8% reported nonadherence to antihypertensive medications. Most of the participants were females (64.3%) and aged 60–69 years old (39.5%). The treatment control (OR: 0.80, 95% CI: 0.7–10.90), patient’s comprehension of hypertension (OR: 0.89, 95% CI: 0.820−0.97), and patient’s emotions (OR: 0.93, 95% CI: 0.88−0.99) were significantly associated with medication nonadherence. No significant associations were observed between the other domains of illness perception and medication nonadherence. Conclusion: Different dimensions of illness perception were associated with non-adherence to antihypertensive medications. Educational interventional should be developed based on patients’ perception of their illness.